The Effect of Social Commerce Construct On Buying Intentions via Consumers Trust in Sellers - Mahyuzar, Heri; Wardoyo, Eko (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Social commerce is the latest development in electronic commerce resulting from the use of social media to interact with fellow users via the internet. The development of these social platforms cannot be separated from the latest advances in ICT and the emergence of web 2.0 technology along with the popularity of social media and social networking sites. Social interactions through social commerce platforms have encouraged consumers to share their personal experiences with others. Many studies have studied e-commerce extensively. However, there is still little research that can identify the characteristics of social commerce that can attract consumer attention. This research aims to examine the influence of the social commerce construct on purchase intentions through consumer trust in sellers. Quantitative data was collected from respondents who live in Kebumen district. Data collection used purposive sampling technique with a research sample of 125 respondents. Data analysis using SEM-PLS. The research results show that the social commerce construct influences purchase intentions, the social commerce construct influences consumer trust in sellers and consumer trust in sellers influences purchase intentions.